2015
DOI: 10.1136/sextrans-2015-052126.235
|View full text |Cite
|
Sign up to set email alerts
|

P191 Survey of genital dermatology training amongst genitourinary medicine (GUM) specialist registrars

Abstract: paramount importance. I am confident that giving students a framework of standard questions and phrases and then allowing them the combined privacy and space to practice the use of such in a safe learning environment will improve their confidence in sexual history taking. Background/introduction Studies exploring public participation in health research have not, to date, included the perspectives of gay and bisexual men taking part in behavioural surveillance research. Understanding factors which motivate men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In 2015, the SIG resurveyed GUM trainees regarding their experience of training in GD 3. The survey identified that training in GD was variable, with mixed confidence in diagnosis, treatment and practical procedures.…”
mentioning
confidence: 99%
“…In 2015, the SIG resurveyed GUM trainees regarding their experience of training in GD 3. The survey identified that training in GD was variable, with mixed confidence in diagnosis, treatment and practical procedures.…”
mentioning
confidence: 99%